2006
DOI: 10.1002/ejoc.200500809
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of the Stereoselectivities of the Diels–Alder Addition of Cyclopentadiene to Ethyl‐(S)‐lactyl Acrylate Catalyzed by Aluminium Chloride

Abstract: We have studied the AlCl 3 -catalyzed cycloaddition of ethyl-(S)-lactyl acrylate (ELA) and cyclopentadiene (CPD) by MP2 and DFT (B3LYP) methods using the 6-31G(d,p) basis set, with or without solvent effects. Four types of dienophileLewis acid (LA) complexes were considered − two types of ELA·AlCl 3 , ELA·2AlCl 3 and ELA·AlCl 2 + . The stereochemical predictions of these models were compared with available experimental data. The participation of lactate-bound ELA·AlCl 3 complexes is insignificant because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…In all cases, the IRC analysis clearly indicates a one‐step mechanism, the reaction asynchronicity ( d 2 – d 1 ) being approximately 0.8. These values are in agreement with other literature data that report DA reactions catalyzed by aluminium trichloride34 and confirm the idea that this catalyst is not able to induce two‐step mechanisms when simple dienophiles are used. However, the LA is very important as it improves the electrophilicity of the unsaturated ketone, thus reducing the activation energy by around 10 kcal mol –1 relative to the uncatalyzed process (see Figure S1 in the Supporting Information).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In all cases, the IRC analysis clearly indicates a one‐step mechanism, the reaction asynchronicity ( d 2 – d 1 ) being approximately 0.8. These values are in agreement with other literature data that report DA reactions catalyzed by aluminium trichloride34 and confirm the idea that this catalyst is not able to induce two‐step mechanisms when simple dienophiles are used. However, the LA is very important as it improves the electrophilicity of the unsaturated ketone, thus reducing the activation energy by around 10 kcal mol –1 relative to the uncatalyzed process (see Figure S1 in the Supporting Information).…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, and considering the vast amount of data now available, it seems improbable that aluminium trichloride, the LA used by the authors, is able to induce a two‐step mechanism when a simple ketone is used as dienophile. Indeed, theoretical approaches clearly indicate that two‐step mechanisms are possible only when the dienophile is strongly activated,52,53 whereas aluminium trichloride is usually involved in one‐step DA processes 34,37. Therefore a two‐step process does not seem very reasonable to us.…”
Section: Discussionmentioning
confidence: 97%
“…[1] Several synthetic and mechanistic studies have been reported, [2,3] and steric and electrostatic effects are accepted to be the major influences determining the observed selectivities. [4][5][6] Usually the chiral auxiliary is connected to the substrate through an amide bond, which has a large impact on the selectivity of these systems. [4,6] Recently, chiral auxiliaries have also started to be used in the formation of carbon-carbon bonds under radical conditions, which has considerably increased their importance in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Usually the chiral auxiliary is connected to the substrate through an amide bond, which has a large impact on the selectivity of these systems. [4,6] Recently, chiral auxiliaries have also started to be used in the formation of carbon-carbon bonds under radical conditions, which has considerably increased their importance in organic chemistry. [7][8][9] The formation of carbon-carbon bonds by free-radical addition to alkenes is of particular importance in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[95][96][97][98] Extending this line of thought to ETC cycloadditions, the reaction shown in Scheme 4.14 allows for an easy control of the electron density difference through appropriate substitution of the Table 4.7 shows a good correlation between high oxidation potential of the styrene and high endo selectivity. The greater selectivity of 52b and 13a has been attributed to their low lying highest occupied molecular orbitals (HOMOs) leading to better SOI with the diene singly occupied molecular orbital (SOMO).…”
Section: Effects Of Secondary Orbital Interaction and Solvents On Endmentioning
confidence: 99%